Pendapatan dan Studi Kelayakan Pertanian Kopi Arabika Kintamani di Kabupaten Bangli Bali - YUDHARI, I DEWA AYU SRI; ANGGRENI, I GUSTI AYU AGUNG LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.1, Juli 2023DO - 10.24843/JAA.2023.v12.i01.p59, 2023)
Income and Feasibility Study of Kintamani Arabica Coffee Farming in Bangli Regency, Bali Plant characteristics in the plantation subsector are classified as perennial and annual crops. Coffee as a plantation commodity has an essential role in the Indonesian economy. Kintamani coffee is grown in a specific area at an elevation of more than 900 meters above sea level. The Kintamani Bali coffee agroecosystem is ideal for Arabica coffee plants and homogeneous farming systems. This study aims to determine how much income Arabica coffee farming generates and assess the feasibility of the business. The research was conducted in Catur Village, Kintamani District, Bangli Regency. The research location was determined by purposive sampling based on the consideration that Catur Village is the largest coffee center and has the largest Arabica coffee plant population in the Kintamani District, Bangli Regency. The respondents of this study were Arabica coffee farmers in Catur Village. The sample was selected by simple random or random sampling, with a sample size of 30 farmers. The results showed that the average income of Kintamani Arabica coffee farming in Bangli Regency was 17,508,497 IDR/year/ha or 1,459,041 IDR/month/ha. The feasibility analysis of Kintamani Arabica coffee farming shows that the R/C ratio was 4.40, the B/C ratio was 3.40, the production BEP was 96.81 kg/ha, and the price BEP was 980.001.20 IDR/year/ha. According to theese findings, Kintamani Arabica coffee farming in Bangli Regency is feasible because it has benefited farmers.